Lactobacillus plantarum GX17 benefits growth performance and improves functions of intestinal barrier/intestinal flora among yellow-feathered broilers - Yin, Yangyan; Liao, Yuying; Li, Jun; Pei, Zhe; Wang, Leping; Shi, Yan; Peng, Hongyan; Tan, Yizhou; Li, Changting; Bai, Huili; Ma, Chunxia; Gong, Yu; et al. (Frontiers in Immunology, 2023)
The Lactobacillus plantarum is recently been found a nature source feed additive bacterial with great advantages in food safety and animal welfare. Seeking novel strains which has commercial application potentiation could benefit local poultry industry, particularly support Chinese farmers. In this study, we tested a recently isolated novel strain of Lactobacillus plantarum GX17, as a feed additive on the growth performance and intestinal barrier functions among 1-day-old Chinese yellow-feather chicks. As good as other commercial probiotics, feeding with Lactobacillus plantarum GX17 shown significant improvements in humoral immune responses and enhancing the immune effect after vaccination for either the Newcastle disease or the avian influenza vaccine. This study also found that feeding with Lactobacillus plantarum GX17 improves the feed-to-weight ratio as well as a significant increase of the villus length to crypt depth ratio. Furthermore, Lactobacillus plantarum GX17 significantly up-regulated the mRNA expression of CLDN, MUC2 and TLR2, all of which are jejunum-associated barrier genes, indicating an improvement of the intestinal barrier functions by enhancing the tight junction between epithelia cells. These results are comparable to the effects of feeding the commercial complex probiotics that improves the expression level of CLDN, ocludin, MUC2, TLR2 and TLR4. In terms of maintaining intestinal health, commercial complex probiotics increased the relative abundance of Parabacteroides and Romboutsia, while Lactobacillus plantarum GX17 increased the relative abundance of Pseudoflavonifractor. Our data suggests that the Lactobacillus plantarum GX17 could enhance the intestinal absorption of nutrients therefore improve the growth performance of Chinese yellow-feather chicks.In conclusion, compared with the commercial complex probiotics, Lactobacillus plantarum GX17 has more positive effects on the growth performance and intestinal barrier function of yellow-feather chickens, and can be used as a feed additive.